Dalagang ina anak na walang magulang - Aguilar, Mila D. Aguilar; Selvido, Ma. Ernie Selvido (Pinoy Tok, 1989)
Shows the unwed mothers at a government-run center, Marillac Hills, Muntinlupa, Metro Manila, and the orphans at a Catholic-run institution, Hospicio de San Jose.